Enhanced anti-metastatic bioactivity of an IGF-TRAP re-engineered to improve physicochemical properties. Issue 1 (December 2018) - Vaniotis, George; Moffett, Serge; Sulea, Traian; Wang, Ni; Elahi, S.; Lessard, Etienne; Baardsnes, Jason; Perrino, Stephanie; Durocher, Yves; Frystyk, Jan; Massie, Bernard; Brodt, Pnina
Abstract The insulin-like growth factor (IGF) axis has been implicated in the progression of malignant disease and identified as a clinically important therapeutic target. Several IGF-1 receptor (IGF-1R) targeting drugs including humanized monoclonal antibodies have advanced to phase II/III clinical trials, but to date, have not progressed to clinical use, due, at least in part, to interference with insulin receptor signalling. We previously reported on the production of a soluble fusion protein consisting of the extracellular domain of human IGF-1R fused to the Fc portion of human IgG1 (first generation IGF-TRAP) that bound human IGF-1 and IGF-2 with a 3 log higher affinity than insulin. We showed that the IGF-TRAP had potent anti-cancer activity in several pre-clinical models of aggressive carcinomas. Here we report on the re-engineering of the IGF-TRAP with the aim of improving physicochemical properties and suitability for clinical applications. We show that cysteine-serine substitutions in the Fc hinge region of IGF-TRAP eliminated high-molecular-weight oligomerized species, while a further addition of a flexible linker, not only improved the pharmacokinetic profile, but also enhanced the therapeutic profile of the IGF-TRAP, as evaluated in an experimental colon carcinoma metastasis model. Dose-response profiles of the modified IGF-TRAPs correlated with their bio-availability profiles, as measured by the IGF kinase-receptor-activation (KIRA) assay, providing a novel, surrogate biomarker for drug efficacy. This study provides a compelling example of structure-based re-engineering of Fc-fusion-based biologics for better manufacturability that also significantly improved pharmacological parameters. It identifies the re-engineered IGF-TRAP as a potent anti-cancer therapeutic.